PENGAWASAN RECORDS BERDASAR PROSES BISNIS ORGANISASI LEMBAGA KEARSIPAN PERGURUAN TINGGI - Seknun, Akbar; Ilmi, Bachrul (Sekolah Vokasi, Universitas Sebelas Maret, 2023)
This research aims to analyze archival supervision carried out by the Open University College Archives (LKPT UT) based on the lifecycle through its business processes in each fostered unit. This research was conducted in January-June 2023 using a qualitative approach. Data in the study were obtained by interviews involving one informant (middle archivist), selected purposively. The results showed that LKPT UT, carried out archive management control at each phase of the archive recycling through internal policies and compliance with legislation and standard rules governing higher education archives, which included the chancellor’s regulation on official manuscripts, archive retention schedules, and archive classification systems based on the archive life cycle within UT. These efforts result in the creation of good archive management at the level of the creator unit so that when the archive reaches LKPT UT, it is well organized. This research can be the basis for similar research on the same subject.